Evaluasi Sistem Keamanan Penerbangan Aviation Security (AVSEC) Untuk Meningkatkan Efektivitas Pelayanan Penerbangan - Akhmad Ivan Zulkarnaen; Eko Prasetyo (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Aviation security is a crucial aspect in the aviation industry that aims to protect passengers, flight crew, and airport facilities from potential threats. The Aviation Security Unit (AVSEC) at the airport plays a vital role in ensuring flight safety through the implementation of strict security procedures. This study aims to evaluate the effectiveness of AVSEC in ensuring flight security at Abdulrachman Saleh Airport, Malang. The method used is qualitative research with a case study approach. Data were collected through in-depth interviews with AVSEC officers, direct observation of the security screening process, and analysis of documents related to AVSEC standard operating procedures (SOP) at the airport. The results of the study indicate that AVSEC officers at Abdulrachman Saleh Airport, Malang have implemented security procedures in accordance with applicable SOPs. However, there are several challenges in its implementation, such as limited human resources, inadequate equipment, and lack of ongoing training for officers. In addition, coordination between AVSEC and other related parties, such as airlines and airport authorities, needs to be improved to ensure the effectiveness of the overall security system. Based on these findings, it is recommended that the management of Abdulrachman Saleh Malang Airport increase resource allocation for AVSEC, update security equipment in accordance with technological developments, and conduct regular training for officers to improve their competence. In addition, it is necessary to conduct periodic evaluations of existing SOPs and strengthen cooperation between related agencies in order to create a safer and more comfortable flight environment for passengers.